Determination of Solid Dispersion by Fluidized Bed Processing: A Platform for Enhancement of Solubility and Dissolution - Rajendra K. Surawase; Kamalkishor G. Baheti (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
This survey article covers the Fluidized bed processing as a novel methodology of solubility enhancement for inadequately water-soluble medications. The main objective of this work was to study the solubility and dissolution kinetics of poorly water-soluble drugs simvastatin from its solid dispersion with different carriers by using fluidized bed processing technique. One of the significant boundaries to accomplish wanted convergence of medication in blood is drug solubility. Among all recently and existing medication up-and-comer around 40% drugs are lipophilic in nature and neglects to arrive at helpful reach because of poor solubility and at last it shows slow dissolution and low bioavailability. Choice of solubility upgrade procedure relies upon drug properties, site of ingestion and required dose structure attributes. Simvastatin is BCS class- II i. e. low soluble and high permeable, which reduces its bioavailability, to overcome this problem, a solid dispersion is formed using various techniques with polymeric carrier to potentially enhance the solubility and dissolution rate such as fluidized bed processing, it will extend drug absorption, therefore the objectives were to make a comparative evaluation among different solid dispersions and to assess the effect of various carriers in solid dispersions on the drug release profile and solubility behaviours. For solid dispersion, Gelucire® 44/14, PVP- K30 and Poloxamer utilized as carrier for poorly water-soluble drugs in order to improve their bioavailability. The dissolution profiles were correlated using various mathematical models such as Zero order, first order, Higuchi and Hixon Crowell model and the Zero order kinetics model gave better correlation results than the other models. Dissolution profile of SIM was significantly improved via complexation with Gelucire 44/14 as compared with the pure drug and other carriers. The binary system which was prepared using FBP showed the highest dissolution rate and solubility profile. It is also concluded that all SDs of SIM showed considerable enhancement in dissolution rate and solubility compared to both PMs and the dissolution rate of both PMs was higher compared to the pure simvastatin.